Conceptual Foundations of Teaching English in Preschool Educational Institutions (Journal of Pedagogical Inventions and Practices, 2022)
The field of pre-school education is considered the primary link of the continuous education system, and it is extremely important in raising a healthy and well-rounded child and preparing him for school. In Uzbekistan, the development of the system of preschool education organizations, attracting children to preschool education organizations, preparing them for school is considered one of the priority tasks of the state policy in the field of education. First of all, favorable conditions are being created to raise a mature generation.